2020
DOI: 10.3390/nu12082182
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Diet-Induced Mild Hyperhomocysteinemia on Vascular Methylating Capacity, Atherosclerosis Progression, and Specific Histone Methylation

Abstract: Hyperhomocysteinemia (HHcy) is a risk factor for atherosclerosis through mechanisms which are still incompletely defined. One possible mechanism involves the hypomethylation of the nuclear histone proteins to favor the progression of atherosclerosis. In previous cell studies, hypomethylating stress decreased a specific epigenetic tag (the trimethylation of lysine 27 on histone H3, H3K27me3) to promote endothelial dysfunction and activation, i.e., an atherogenic phenotype. Here, we conducted a pilot study to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 49 publications
(97 reference statements)
3
25
0
Order By: Relevance
“…In fact, the LMKD was formulated to induce mild HHcy by decreasing the levels of vitamins B6, B9 and B12 in the presence of excess methionine. Previous studies [10,13,17] have also reported a significant decrease in the body weight of animals fed vitamin-B deficient diets. Thus, the very high fat content in the LMKD used here did not counterbalance the deleterious effect on the growth of a dietary treatment with suboptimal levels of micronutrients.…”
Section: Body Weightmentioning
confidence: 77%
See 2 more Smart Citations
“…In fact, the LMKD was formulated to induce mild HHcy by decreasing the levels of vitamins B6, B9 and B12 in the presence of excess methionine. Previous studies [10,13,17] have also reported a significant decrease in the body weight of animals fed vitamin-B deficient diets. Thus, the very high fat content in the LMKD used here did not counterbalance the deleterious effect on the growth of a dietary treatment with suboptimal levels of micronutrients.…”
Section: Body Weightmentioning
confidence: 77%
“…Previous studies have addressed the atherogenic impact of mild Hcy and the underlying epigenetic deregulation in the absence of nutritional ketosis [7]. These include our recent study, in which we used a hypomethylating high-fat diet, but in which the presence of dietary carbohydrates precluded the establishment of nutritional ketosis [13]. The present research innovates by investigating the vascular effects of a hypomethylating high-fat diet, in which a markedly different dietary macronutrient profile, i.e., the absence of carbohydrates, triggers a stage of ketosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end-point mice were euthanized by carbon dioxide inhalation and aortas were collected as previously described in detail [ 33 ]. Inguinal subcutaneous WAT and interscapular BAT were removed and immediately snap-frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Aortas were processed as previously described in detail [ 33 ]. Briefly, dissected aortas were equilibrated to 0.1% Magnevist (Bayer HealthCare Pharmaceuticals Inc., Whippany, NJ, USA), 0.25% sodium azide, PBS solution overnight at 4 °C, and plaque volume was determined by MRI using an Agilent 14T micro imaging system (Agilent Technologies, Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%